2013
DOI: 10.1186/1748-717x-8-231
|View full text |Cite
|
Sign up to set email alerts
|

MiR-34a is up-regulated in response to low dose, low energy X-ray induced DNA damage in breast cells

Abstract: BackgroundMicroRNAs are non-coding RNAs involved in the regulation of gene expression including DNA damage responses. Low doses of low energy X-ray radiation, similar to those used in mammographic exams, has been described to be genotoxic. In the present work we investigated the expression of miR-34a; a well described p53-regulated miRNA implicated in cell responses to X-ray irradiation at low doses.MethodsNon-cancerous breast cell line MCF-10A and cancerous T-47D and MCF-7 cell lines were submitted to a low-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 45 publications
3
31
0
Order By: Relevance
“…IR treatment on mouse could upregulate the family of miR‐34, including miR‐34a‐3p, miR‐34a‐5p, miR‐34b‐3p, and miR‐34c‐3p. The results validated by the qRT‐PCR were in consistent with former studies (Stankevicins et al, ). In fact, accumulating evidence informed that miR‐34a could be induced by IR in vitro and in vivo (He et al, ; Cong et al, ).…”
Section: Resultssupporting
confidence: 91%
“…IR treatment on mouse could upregulate the family of miR‐34, including miR‐34a‐3p, miR‐34a‐5p, miR‐34b‐3p, and miR‐34c‐3p. The results validated by the qRT‐PCR were in consistent with former studies (Stankevicins et al, ). In fact, accumulating evidence informed that miR‐34a could be induced by IR in vitro and in vivo (He et al, ; Cong et al, ).…”
Section: Resultssupporting
confidence: 91%
“…The tumor itself is a known source of circulating miRNAs. In vitro experiments have notably demonstrated that several tumor cell lines exposed to cytotoxic agents or ionizing radiation re‐expressed miR‐34a (Tazawa et al, ; Ghawanmeh et al, ; Chiyomaru et al, ; John‐Aryankalayil et al, ; Stankevicins et al, ; Wang et al, ). Our team also observed miR‐34a overexpression in breast tumor tissues after the NAC.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated that LDIR exposure alters miRNA levels, which ultimately leads to modified protein expression profiles. miRNAs such as miR-21, miR-34a, miR-29c, miR-16, miR-202, miR-303 and miR-572 are all LDIRresponsive miRNAs implicated in radiation-induced altered gene regulation (92)(93)(94)(95). Interestingly, LDIR-mediated miRNA alterations demonstrate temporal regulation.…”
Section: Effects Of Ldir On Epigenetic Gene Regulationmentioning
confidence: 99%